Aberrant Methylation of MEG3 Functions as a Potential Plasma-Based Biomarker for Cervical Cancer - Zhang, Jun (Sci Rep, 2017)
Methylation alterations of specific genes have recently been identified as diagnostic biomarkers for human cancers. Although MEG3 has been proved to be a tumor suppressor in cervical cancer according to our previous study, the diagnostic value of MEG3 methylation in plasma is still unknown. Therefore, the aim of this study is to identify a novel epigenetic biomarker for cervical cancer. In the current study, the level of MEG3 methylation was evaluated using methylation-specific polymerase chain reaction. The results showed that the level of MEG3 methylation was significantly higher in cervical cancer tissues and patients’ plasmas than those in adjacent normal tissues and plasmas of healthy participants respectively. Moreover, the accuracy was good enough for MEG3 methylation in plasma to discriminate CIN III patients from healthy participants. In addition, MEG3 methylation in plasma also has high discriminating power to predict HR-HPV infection and lymph node metastasis. Furthermore, hypermethylation of MEG3 in plasma was associated with worse recurrence-free and overall survival in cervical cancer patients. In conclusions, MEG3 methylation in plasma can serve as a diagnostic and prognostic biomarker for cervical cancer, providing useful information for clinical management.